1986
DOI: 10.1177/00220345860650120201
|View full text |Cite
|
Sign up to set email alerts
|

1985 Kreshover lecture. Molecular Factors Influencing Neutrophil Defects in Periodontal Disease

Abstract: Major advances in our understanding of the role of the neutrophil in host defense against periodontal organisms have been made through studies of localized juvenile periodontitis (LJP). Several lines of evidence suggest that LJP is an infectious process closely associated with Actinobacillus (Haemophilus) actinomycetemomitans as a causative agent, although other organisms may also participate. The immunologic profile of LJP patients suggests that a cell-associated neutrophil locomotory dysfunction is a key und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
1
3

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 121 publications
1
73
1
3
Order By: Relevance
“…The initiation and progression of periodontitis do not always occur in the same manner, because the host defensive mechanism varies among patients and race (Page et al 1985;Genco et al 1986, Genco, 1992; hence this study was designed to evaluate the numerical value of the defense cells in juvenile and non-juvenile periodontitis patients compare with the expected normal values in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The initiation and progression of periodontitis do not always occur in the same manner, because the host defensive mechanism varies among patients and race (Page et al 1985;Genco et al 1986, Genco, 1992; hence this study was designed to evaluate the numerical value of the defense cells in juvenile and non-juvenile periodontitis patients compare with the expected normal values in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving monozygotic and dizygotic twins have suggested that about half of the population variance in disease could be accounted for by genetic factors (8,24). Increased susceptibility to periodontal disease is found in conjunction with several inherited diseases (10,28). Very recently, an interleukin-1 polymorphism has been reported to be a predictor of future severity in adult periodontal disease (19).…”
mentioning
confidence: 99%
“…This mechanism could exist in physiological conditions as a new negative feedback mechanism of inflammation. Early-onset periodontitis is characterized by severe, rapidly progressive, early-onset alveolar bone loss and familial aggregation (50). PMNs from early-onset periodontitis patients have been reported to produce much higher HLE than controls (51).…”
Section: Discussionmentioning
confidence: 99%